Evaluation of the Efficacy of Beauveria bassiana in Controlling the Periplaneta Americana in Iraq (Indian Journal of Forensic Medicine & Toxicology, 2020)
The current study was conducted from the ninth month of the year 2019 to the end of the sixth month of 2020aiming and evaluating the effectiveness of the fungus Beauveria bassiana in controlling the Periplanetaamericana.More than 250 samples were collected, and the most of them were collected for the purpose of studyingBiology control. The fungus Beauveria bassiana was used in the control, where the fungus was used in fourdifferent concentrations and kneaded by mixing with water and dilution, where the concentrations wereused (0.25 × 107, 0.5 × 107, 0.75 × 107.1 × 107) and all recorded death rates of 100% in nymphs after thepassage of (244,168,120,96) respectively, and in adults, a murder rate was recorded after (244,192,144,120)hours respectively, and there were significant differences in the percentage of homicide between adults andnymphs.
Keywords: Periplaneta americana. Beauveria bassiana . Cockroaches